(untitled) (Journal on studies and research of academic knowledge, 2022)
The research was carried out with the objective of determining the amount of carbon in biomass of the native forest of the Boquerón company, district of Isla Umbú, Ñeembucú, Paraguay in 2016. The following variables were analyzed: amount of carbon in biomass and amount of carbon in soil, total and stem height of the studied species, diameter at breast height and soil sampling by conducting test pits at a depth of 2 meters and extraction at 20 cm of sample, for analysis in the Soil and Water Laboratory of the Faculty of Agricultural Sciences and Rural Development of the National University of Pilar. Results show that the native forest of the Boquerón district has an average of 61,330 tons of carbon per hectare in biomass and 1.275% carbon in soil